Social Responsibility and Human Talent Management in the Provincial Municipality of Canas, Cusco - Méndez-Gutiérrez, Leidy Lucia; Soncco Champi, Roni (LACCEI, 2025)
This research aims to determine the relationship between human talent management and social responsibility in the Provincial Municipality of Canas, Cusco, in 2024. The study adopts an applied research approach with a quantitative, correlational, and cross-sectional methodology. The population consists of 89 employees, both permanent and contracted, selected through non-probabilistic convenience sampling. Data was collected using a survey and analyzed using descriptive statistics and Spearman’s correlation test. The results indicate that 64% of employees perceive a medium level of human talent management, while 69.7% report a medium level of social responsibility. A moderate positive correlation (ρ = 0.316, p = 0.003) was found between both variables. This suggests that effective human talent management fosters an ethical, committed, and socially responsible work environment. The study highlights the need for continuous professional development and sustainable initiatives to strengthen municipal governance.